3D printed scaffolds with gradient porosity based on a cellulose nanocrystal hydrogel. Issue 9 (16th February 2018) - Sultan, Sahar; Mathew, Aji P.
Abstract : 3D printed hydrogel scaffolds with gradient porosity and aligned cellulose nanocrystals. Abstract : 3-Dimensional (3D) printing provides a unique methodology for the customization of biomedical scaffolds with respect to size, shape, pore structure and pore orientation useful for tissue repair and regeneration. 3D printing was used to fabricate fully bio-based porous scaffolds of a double crosslinked interpenetrating polymer network (IPN) from a hydrogel ink of sodium alginate and gelatin (SA/G) reinforced with cellulose nanocrystals (CNCs). CNCs provided favorable rheological properties required for 3D printing. The 3D printed scaffolds were crosslinked sequentially via covalent and ionic reactions resulting in dimensionally stable hydrogel scaffolds with pore sizes of 80–2125 μm and nanoscaled pore wall roughness (visible from scanning electron microscopy) favorable for cell interaction. The 2D wide angle X-ray scattering studies showed that the nanocrystals orient preferably in the printing direction; the degree of orientation varied between 61–76%. The 3D printing pathways were optimised successfully to achieve 3-dimensional scaffolds ( Z axis up to 20 mm) with uniform as well as gradient pore structures. This study demonstrates the potential of 3D printing in developing bio-based scaffolds with controlled pore sizes, gradient pore structures and alignment of nanocrystals for optimal tissue regeneration.